Structural grades of timber by bending and compression tests - Branco, Jorge M. (2006)
This paper presents the results obtained in a series of tests on Pinus Pinaster Ait. timber specimens, using the prEN408:2000, to estimate the local and global Young’s modulus and strength both in bending and compression parallel to the grain. The results obtained are compared with the values presented in the Portuguese Nationally Determined Parameters of Eurocode 5, for the quality classes assign by Portuguese Standard NP4305:1994 by visual grading.